2010
DOI: 10.1029/2010gl045052
|View full text |Cite
|
Sign up to set email alerts
|

Importance of location for describing typical and extreme wind speed behavior

Abstract: [1] Several recent studies have considered the potential impact of climate change on regional wind intensity. However, previous wind speed studies in the Pacific Northwest (PNW) present conflicting results for wind speed trends in relation to climate drivers. This study analyzes the percentiles (50th, 75th, and 95th) of the strongly positively skewed distributions for PNW maximum daily wind speeds from 92 meteorological stations, and reveals different behaviors for average and extreme wind speeds. Considerably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
1
19
1
Order By: Relevance
“…Previous studies also detected a more statistically significant atmospheric stilling over coastal stations (e.g. Griffin et al, ; Minola et al, ).…”
Section: Methodssupporting
confidence: 75%
“…Previous studies also detected a more statistically significant atmospheric stilling over coastal stations (e.g. Griffin et al, ; Minola et al, ).…”
Section: Methodssupporting
confidence: 75%
“…In addition to the negative trends found in the ground-based observation record, Pryor et al (2009) also showed the dominance of positive trends in the National Centers for Environmental PredictionNational Center for Atmospheric Research (NCEP-NCAR) reanalysis and the 40-yr European Centre for Medium-Range Weather Forecasts (ECMWF) ReAnalysis (ERA-40) for the 50th-percentile and 90th-percentile annual mean wind speed and further found that wind speed trends at 0000 and 1200 UTC from the North American Regional Reanalysis (NARR) are opposite in sign over the west. Overall, past studies support the synthesis by Pryor et al (2009) that the surface wind speeds over the continental United States exhibit different and sometimes opposite trends depending on the dataset used, the time period examined, and the region of interest (Pryor et al 2007;McVicar et al 2008;Pryor et al 2009;Li et al 2010;Griffin et al 2010).…”
Section: Introductionmentioning
confidence: 69%
“…Only the linear trends at the 90% significance level or higher are considered to be statistically significant [similar to what what is used in Pryor et al (2009)], using a two-tailed t test for each grid point. OLS is widely used in the analysis of wind trend (McVicar et al 2008;Pryor et al 2009;Li et al 2010), but Pryor and Ledolter (2010) and Griffin et al (2010) recently noted that significant temporal autocorrelation of wind may occur in a time span of 30 years, depending on the geographical location, and must be filtered out of the time series before applying OLS; otherwise, the temporal autocorrelation may exaggerate the statistical significance of the trend.…”
Section: B Methods For Analysis Of Wind Trendmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistically significant trends were defined as those where p < 0.05 (in bold and in parenthesis) and p < 0.10 (in bold) 1948-2014 1989-2014 1948-2014 1989-2014 1948-2014 1989-2014 features (e.g., surface roughness; Wever 2012) against prevailing wind flows (Griffin et al 2010). Therefore, even though the role of surface roughness (Vautard et al 2010) on the global decline of wind speed over land when compared to the ocean surfaces has not been observed in this study, both simulations and observations revealed that local features play a key role in the reported trends (confirming results of Vautard et al 2010;Griffin et al 2010;Wever 2012). For example, high-spatial resolution hindcast products, particularly those downscaled from SeaWind II at 15-km horizontal grid-spacing, demonstrated the orographic effects of the Canary Islands on small-scale atmospheric processes in ocean winds (Chelton et al 2004).…”
Section: Discussionmentioning
confidence: 99%